2006
DOI: 10.1002/ejic.200500833
|View full text |Cite
|
Sign up to set email alerts
|

DFT Calculations of the 183W NMR Chemical Shifts in Reduced Polyoxotungstates

Abstract: 6-with different degrees of (de)localization of the electrons introduced. Despite some discrepancies in the calculated and experimental data, the calculations adequately describe the changes in the chemical shifts upon reduction. The reduction of a fully oxidized anion is accompanied by an expansion of the geometry. The effect of the charge localiza-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This had the additional advantage of being consistent with other related computational work on POMs 7. 9, 33, 34, 5458…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This had the additional advantage of being consistent with other related computational work on POMs 7. 9, 33, 34, 5458…”
Section: Resultssupporting
confidence: 82%
“…Similar findings were recently reported by Poblet and Kazansky and their co‐workers 33. 34 All these observations consistently illustrate that solvation effects and the level of relativistic treatment play an important role. It was the purpose of this work to show how these problems can be overcome.…”
Section: Introductionsupporting
confidence: 90%
“…This may be due to the slightly weak interaction between Re and its adjacent atoms compared with related bonds in PW 12 . As Poblet demonstrated that the reduction of a fully oxidized anion is accompanied by an expansion of the geometry, [33] the bonds in single-and double-electron reduced polyanions of PW 11 ReN are elongated. So, the reduced polyanions are loosened by adding reduced electrons.…”
Section: Resultsmentioning
confidence: 98%
“…In the present study we will make use of the previous experience [32][33][34][35] to find the best methodology for computing accurate d( 31 P) of solvated POMs. The task is even more complicated because POMs are negatively charged polyanions that must be modelled in the presence of a stabilising medium to accurately reproduce their features.…”
Section: Introductionmentioning
confidence: 99%